The influence of Helicobacter pylori infection on acute coronary syndrome and lipid metabolism in the Chinese ethnicity - Fang, Yizhen; Fan, Chunming; Li, Yun (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundAcute coronary syndrome (ACS) patients frequently present a relatively high prevalence of Helicobacter pylori (H. pylori) infection. H. pylori was previously hypothesized to induce ACS through the regulation of lipid levels. However, the risk of H. pylori-induced ACS varies significantly among different ethnic groups, and the associations between H. pylori and lipid parameters remain unclear. This study aimed to systematically assess the risk of ACS in Chinese populations with H. pylori infection while also evaluating the effects of H. pylori on lipid parameters.Materials and methodsA hospital-based case−control study involving 280 participants was conducted. Immunoblotting was used for the detection and genotyping of H. pylori. The associations between H. pylori and ACS, as well as lipid parameters, were analyzed via the chi-square test and a multiple logistic regression model.ResultsH. pylori infection significantly increased the risk of ACS among all participants (adjusted odds ratio (OR) = 4.04, 95% confidence interval (CI): 1.76−9.25, P < 0.05), with no associations with virulence factors (cytotoxin-associated gene A (CagA) or vacuole toxin geneA (VacA)). Subgroup analysis revealed a significant increase in the risk of ACS among the elderly population aged 56−64 years with H. pylori infection. Additionally, a substantial association was observed between H. pylori and acute myocardial infarction (AMI). No significant differences were found in lipid parameters, including low-density lipoprotein cholesterol (LDL-C), triglyceride (TG), total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), and the LDL/HDL ratio, between individuals positive and negative for H. pylori infection. Similar results were observed between the ACS group and the control group.ConclusionsOur study has demonstrated for the first time that H. pylori does not significantly impact lipid metabolism but increases the risk of ACS fourfold in the Chinese population (OR = 4.04, 95% CI: 1.76−9.25). Furthermore, the virulence factors of H. pylori (CagA and VacA) may not be involved in the mechanisms by which they promote the development of ACS. This finding provides additional evidence for the association between H. pylori and ACS among different ethnic groups and refutes the biological mechanism by which H. pylori affects ACS through lipid metabolism regulation. Regular screening for H. pylori and eradication treatment in elderly individuals and those at high risk for ACS may be effective measures for reducing the incidence of ACS. Future research should include multicenter randomized controlled trials and explore host genetics and the effects of H. pylori on the gut microbiota as potential biological pathways linking H. pylori and ACS.